Protective role of appendicectomy on onset and severity of ulcerative colitis and Crohn's disease - Graham Radford‐Smith (2002)
Recent studies on appendicectomy rates in ulcerative colitis and Crohn's disease have generally not addressed the effect of appendicectomy on disease characteristics. The aims of this study were to compare appendicectomy rates in Australian inflammatory bowel disease patients and matched controls, and to evaluate the effect of prior appendicectomy on disease characteristics.Patients were ascertained from the Brisbane Inflammatory Bowel Disease database. Controls matched for age and sex were randomly selected from the Australian Twin Registry. Disease characteristics included age at diagnosis, disease site, need for immunosuppression, and intestinal resection.The study confirmed the significant negative association between appendicectomy and ulcerative colitis (odds ratio (OR) 0.23, 95% confidence interval (CI) 0.14-0.38; p<0.0001) and found a similar result for Crohn's disease once the bias of appendicectomy at diagnosis was addressed (OR 0.34, 95% CI 0.23-0.51; p<0.0001). Prior appendicectomy delayed age of presentation for both diseases and was statistically significant for Crohn's disease (p=0.02). In ulcerative colitis, patients with prior appendicectomy had clinically milder disease with reduced requirement for immunosuppression (OR 0.15, 95% CI 0.02-1.15; p=0.04) and proctocolectomy (p=0.02).Compared with patients without prior appendicectomy, appendicectomy before diagnosis delays disease onset in ulcerative colitis and Crohn's disease and gives rise to a milder disease phenotype in ulcerative colitis.